Acid‐Triggered Charge‐Convertible Graphene‐Based All‐in‐One Nanocomplex for Enhanced Genetic Phototherapy of Triple‐Negative Breast Cancer. Issue 1 (4th December 2019) - Wu, Chunhui; Tian, Yuan; Zhang, Yingxue; Xu, Jiming; Wang, Yikun; Guan, Xiaotian; Li, Tingting; Yang, Hong; Li, Shun; Qin, Xiang; Liu, Yiyao
Abstract: Highly efficient and stimulus‐responsive nanomedicines for cancer treatment are currently receiving tremendous attention. In this study, an acid‐triggered charge‐reversible graphene‐based all‐in‐one nanocomplex is appropriately designed by surface modification with multilayer polymers and simultaneous co‐transportation of photosensitizer indocyanine green (ICG) and oligonucleotide inhibitor of miR‐21 (miR‐21i) to achieve highly efficient genetic phototherapy in a controlled manner. The nanocomplex (denoted as GPCP/miR‐21i/ICG ) effectively protects miR‐21i from degradation and exhibits excellent photothermal/photochemical reactive oxygen species (ROS) generation as well as fluorescence imaging ability. The cargoes ICG and miR‐21i can significantly be released at acidic pH compared with normal physiological medium and escaped from endosomes/lysosomes due to the acid‐triggered charge reversal effect. Typically, the released miR‐21i downregulate the endogenous miR‐21 and result in the upregulation of the target proteins PTEN and Bax, thus increasing the phototherapeutic efficiency of ICG. High in vivo anticancer efficiency against the MDA‐MB‐231 triple‐negative breast cancer (TNBC) model is obtained due to the combination of genetic regulation of miR‐21i and the photokilling effect of ICG. This work highlights the great potential of this smart nanocomplex as an attractive modality of gene‐photo combined treatment of cancer, especially for intractable TNBC. Abstract : A novel acid‐triggered charge‐reversible graphene‐based all‐in‐one nanocomplex is appropriately designed for simultaneous and controlled delivery of photosensitizer and oligonucleotide inhibitor of miR‐21. Enhanced phototherapeutic efficiency both in vivo and in vitro is achieved by antagonizing the miR‐21 signal axile, thus displaying prominent therapeutic advantages of cancer gene‐photo combination treatment, especially for the intractable triple‐negative breast cancer.